Kahl, T., Lozovanu, D., Heuberger, V., Jordan, P., Ethnisches Bewusstsein in der Republik Moldau im Jahr 2004 / Ethnic Consciousness in the Republic of Moldova in 2004 - Tátrai, Patrik (Hungarian Geographical Bulletin, 2012)
-